Non-melanoma skin cancer treated with mohs micrographic surgery in Thailand - Piyaroj Sethabutra (2019)
© 2018, Medical Association of Thailand. All rights reserved. Background: Long-term follow-up, complications, and patient satisfaction are essential outcome measures regarding the benefits of Mohs micrographic surgery [MMS] for treating non-melanoma skin cancers [NMSCs]. Objective: To report risk factors, clinical findings, and follow-up outcomes of all NMSC patients treated with MMS. Materials and Methods: The present retrospective study included all patients in the outpatient Dermatology Clinic of Siriraj Hospital, Bangkok, Thailand, with NMSC treated with MMS between 2008 and 2013. The outcomes measured were patient demographic data, duration of tumor, recurrence of tumor before MMS, number of lesions, risk factors for developing skin cancer, histological type and subtype, location of tumor, pre-operative and post-operative size, method of closure, operative time, 5-year recurrence rate after MMS, complications, and patient satisfaction. Results: The present study included 108 patients (63% females and 37% males) with a mean age of 70±12 years (range 36 to 93 years). The mean duration of tumor was 37±60 months (range 0.5 to 480 months). Basal cell carcinoma [BCC] comprised 95.1% of cases, whereas squamous cell carcinoma [SCC] was 4.9%. The significant risk factor for both BCC and SCC was sun exposure. The most common locations for both BCC and SCC were the head and neck regions. The most common subtype for BCC was a non-aggressive subtype, 47%. The most commonly used method of closure was second intention, 28 cases (22.8%). The mean operative time was 116.13 minutes (range: 30 to 360 minutes). During the longest follow-up time (60 months), the recurrence rate was 0.81%. There were no major complications. The majority (96.4%) of patients gave a 75% to 100% satisfaction rate after surgery. Conclusion: The present study demonstrates less than one percent recurrence rate in NMSCs treated with MMS and the necessity of margin control in high-risk tumors.